THE AFFECTING FACTORS ON THE INFECTION WITH THE HELICOBACTER PYLORI IN THE AL-RAMADI CITY - DHUHA A. OBAID; ESSAM M. ABDULAAH; MOHAMED Q. ABED (مجلة جامعة الانبار للعلوم الصرفة, 2015)
The study aims at finding out some the affecting factors on the infection with the Helicobacter pylori . It also includes age since the highest rate was for age group (11-20 years). The factor of sex has also an effect because females showed a higher proportion of infection over males of 70% and 30 % respectively. The kind of food has relation to the development of the H.pylori with percentage 37%. Smoking has also relation to the infection of 26%. There was also a relationship between the infection and the place of residence because the percentage of infection in villages is higher than in towns of 60% and 40% respectively. The study also concentrates on some immune diseases associated with infection of the H.pylori. since there is a relationship between the infection H.pylori and diabetes of 40%.